(In)effective Planning Capacity of CSDP Missions: Comparative Analysis of EULEX Kosovo and EUFOR Althea - Boštjančič Pulko, Ivana (Journal of Regional Security, 2018)
This paper evaluates the planning capacity of two Common Security and Defence (CSDP) missions (EULEX Kosovo and EUFOR Althea) in order to assess the effectiveness of CSDP planning process. Both missions suffer due to partial interests within the EU and low po- sitioning of CSDP on political agendas of the member states. Compared to NATO, EU missions’ political control is more much detailed once the mission is deployed. CSDP planning architec- ture has been considerably reformed since the inception of the first missions in 2003, however the supervision by the member states is still present in all phases of restructuring and imple- mentation. EULEX planning process includes a well elaborated lessons learnt process, however the implementation of the findings on the operational level is rather weak whereas EUFOR Althea profited mostly from the access to NATO planning assets. CSDP missions are political missions and their effectiveness seems to be of secondary importance to the EU member states.